Time Difference Test for Achieving Bromage Score 0 Post-Caesarea Sectio Using Method Eracs and Non Eracs to Women Abandoned at Simpang Lima Gumul (SLG) Kediri Hospital - Aprin Rusmawati; Tri Wijiastutik; Windy Ari Wijaya; Alfian Fawzi (Journal Of Nursing Practice, 2024)
Background: The assessment criteria used in determining the readiness of a patient under spinal anesthesia to be discharged from the recovery room is the Bromage score. Delays in moving patients can cause additional treatment costs recovery room, hypothermia, and anxiety in patients. Purpose: This research aims to determine differences in achievement time. Bromage scored 0 post-cesarean sections with the ERACS method and not ERACS for mothers giving birth at RSUD SLG Kediri. Method: This research uses a design true experiment with a type posttest-only control group. With purposive sampling A sample of 60 respondents was obtained, divided equally between experimental groups and methods ERACS and the control group with the Non method ERACS, and statistical tests were carried out by Mann-Whitney. Results: The results of research from 60 respondents showed that the majority of patients who used the ERACS method reached a bromage score of 0 within 26-35 minutes after spinal anesthesia. Meanwhile, the majority of patients who use non-methods ERACS reach a bromage score of 0 in 126-135 minutes. Statistical test analysis Mann-Whitney The significance results obtained were p value=0.000 (<0.05), meaning that there was a significant difference in time to achievement bromage score 0 in patients with cesarean section method ERACS and non-RACS. Conclusion: Achievement time Bromage score 0 post spinal anesthesia methods ERACS an average of 30.00 minutes faster than the Nonmethod ERACS. Based on this time difference, the anesthetist can provide information regarding the duration of the achievement time Bromage score and estimated patient transfer time.